PENGEMBANGAN LAMBANG-LAMBANG BUDDHIS UNTUK SEKOLAH MINGGU BUDDHA ADHICITTA - Fajar, Wahyu; Parsiyono, Parsiyono; Dewi, Sukhitta (Jurnal Pencerahan, 2021)
The limited learning media containing Buddhist symbols materials in the Buddhist Sunday Schools causes the lack of visualization in children's learning material. One alternative is to use an application creation program that utilizes Adobe Flash. Based on this problem, a learning media for Buddhist symbols was developed for the Adhicitta Buddhist Sunday School, Kenteng Village, Susukan District, Semarang Regency. This research is research and development. Data collection instruments used questionnaires and documentation and were analyzed using descriptive statistics. The data collection technique was carried out by the ADDIE process to see the level of the product validity and its development stage and to use a questionnaire for the success of the learning media. The results of the learning media validation of Buddhist symbols showed 81.176% of the Material Experts and the results of the validation of the media expert show that the learning media developed was feasible with an average acquisition of 80%. Based on the results of research conducted, it can be concluded that the learning media of Buddhist symbols can be used in the Buddhist Sunday School learning program.